La política de humedales de Bogotá, un reto de gerencia pública (2021)
Bogotá has a system of 13 recognized wetlands, of which 11 are in the Ramsar category. The care and protection of these ecosystems affects the good management of the city's water system, they function as buffers in floods and provide important ecosystem services. The District Secretary for the Environment, together with other entities of the district, are in charge of guaranteeing its recovery and proper functioning. In 2004, the District Secretary for the Environment began the process of elaborating the District's Wetlands Policy, in order to respond to the problems faced by the Bogotá wetlands in terms of their use and management. Its objective is to guide and regulate the actions that are carried out in these ecosystems to achieve their preservation and conservation. Decree 624 was issued in 2007 and after more than 13 years of its approval, its implementation continues to be a challenge...